Vulnerabilidade socioambiental e suscetibilidade a seca e a estiagem no estado do Ceará - Silva, Cicera Celiane Januário da (2023)
To understand the dynamics and transformations that occur in society and for the purpose of social and environmental decision-making studies on socio-environmental vulnerability are essential. The spatial focus of this research is the state of Ceara, considering the experience of drought in this region, which is my place of birth, along with the frequent occurrence of droughts and dry spells that affect the municipalities of Ceara, combined with the fact that its territory is mostly located in the Brazilian senuarid region. Within this perspective, the objective of the research is to analyze the different degrees of socio-environmental vulnerability in the state of Ceara, considering the scenario of susceptibility to drought and dry spells. To achieve the proposed objectives, the work has been divided into three stages: (1) Identification of social vulnerability, (II) Identification of municipalities susceptible to drought and dry spells, (III) Mapping of socio-environmental vulnerability to drought and dry spells. For the stage of identifying social vulnerability, three dimensions were considered that reflect the conditions of infrastructure, income, and social situation in Ceara These dimensions consist of variables extracted from the IBGE Automatic Recovery System SIDRA based on the 2010 census data Susceptibility analysis was carried out based on the Consecutive Dry Days (CDD) for a temporal period of 32 years (1990 to 2021), using daily rainfall data provided by the Cearense Foundation for Meteorology and Water Resources (FUNCEME). In the context of social vulnerability, the state of Ceará has 84% of its municipalities classified as being in undesirable social vulnerability conditions, meaning they have a high degree of vulnerability in the high and very high categories. The income dimension was the most significant factor compared to the other dimensions, as 98% of municipalities in Ceará have undesirable income conditions. Regarding susceptibility, Ceará has a high number of municipalities susceptible to drought and dry spells based on the CDD analysis. By overlapping the scenarios of social vulnerability and susceptibility to drought and dry spells, it was possible to identify the municipalities with the highest degree of socio-environmental vulnerability. It was found that 44% of the state is in a high degree of socio-environmental vulnerability, and an additional 14% is in a very high degree. Thus, through this research, it was possible to reinforce and identify the municipalities that require the most attention from the government, highlighting the need for structural transformations and actions aimed at reducing damages and providing more alternatives for living with drought.